Pengaruh Pemberian Pakan Komplit Berbahan Dasar Lamtoro dan Silase Jerami Jagung dengan Imbuhan Zn Biokompleks Terhadap Konsumsi Serta Kecernaan BETN dan Energi Ternak Kambing Lokal Jantan - Sari, Rosalia Supia; Yunus , Marthen; Amalo, Daud; Maranatha, Grace (Animal Agricultura, 2024)
The purpose of this experiment was to determine the effect of giving a complete feed containing leucaena forage and corn straw silage with different constellations with biocomplex Zn addition on the digestibility of nitrogen free extract and Energy of male local both. The research method used was the Latin square design with 4 treatments and 4 periods as repetition. The four treatments were: P0: leucaena 100% (control) + Zn biocomplex 100 mg, P1 : leucaena 70% + silage corn straw 20% + 10% + concencrate + Zn biocomplex 100 mg, P2 : leucaena 60% + corn straw silage 30% + concetrate 10% + Zn biocomplex 100 mg, P3: leucaena 50% + corn straw silage 40% + concentrate 10% + Zn biocomplex 100 mg. The average value of each variable in each treatment is nitrogen free extract (g/h/d) P0 consumption; (280.12±20.53), P1; (327.86±23.79), P2; (326.14±22.89), P3; (322.08±24.05); P0 Energy consumption (Kcal/h/d): (2356.34±172.71), P1 ; (2816.01±204,30), P2 ; (2826.70±199.17), P3 ; (2817.09±210.40); While, nitrogen free extract digestibility (%), P0 ; (75.79±3.25), P1 ; (78.90±0.88), P2 ; (79.41±1.48), P3 ; (78.99±1.58); P0 Energy Digestibility(%) (69.50±7.77), P1 ; (76.27±3.59), P2 ; (76.51±2.86), P3 ; (74.67±8.75). The data obtained were analyzed using analysis of variance showing that the treatment had on sigificant effect on the consumption and digestibility of nitrogen free extract and energy (P>0.05). The conclusion of this study was that providing complete feed made from leucaena corn straw silage up to 40% and 10% concentrate with Zn biocomplex 100 mg added provided nitrogen free extract consumption and anxiety and energy similar to that of 100% leucaena given to local both.